Pengaruh Konflik Peran Ganda Dan Beban Kerja Terhadap Kinerja Karyawan Wanita Dengan Kelelahan Emosional Sebagai Variabel Mediasi (Studi Pada PT. Keong Nusantara Abadi Wongcoco) - Khusna, Okta Amalia; Nurhayati, Nurhayati (Universitas Mitra Indonesia, 2024)
Human Resources are an important factor in a company. In order for the activities within the company to run well, employees in the company must have competent abilities in their field, because the success of a company is greatly influenced by employee performance. Formulation of the problem in this research: Does dual role conflict influence employee emotional fatigue, Does workload influence employee emotional fatigue, Does emotional fatigue influence employee performance, Does dual role conflict influence employee performance, Does workload influence employee performance, Does The role of emotional exhaustion mediates the effect of dual role conflict on employee performance. Does the role of emotional exhaustion mediate the effect of workload on employee performance. This research is quantitative research, the population in this research is all female production employees. The technique used was a saturated sample and a sample of 89 employees was obtained. And the analysis in this research uses SEM model analysis using SmartPLS version 4.0. The research results obtained directly from each variable, namely KPG (X1) have a positive and significant effect on KE (M), BK have a positive and significant effect on KE (M), KE (M) have a negative and significant effect on KK (Y), KPG ( * , KE (M) mediates the influence of BK (X2) on KK through (Y) full mediation. Keywords: Dual Role Conflict, Workload, Emotional Exhaustion, and Employee Performance